PENGARUH LITERASI KEUANGAN, RELIGIUSITAS DAN PENDAPATAN TERHADAP MINAT INVESTASI DI PASAR MODAL SYARIAH (Studi Pada Masyarakat Milenial Kota Semarang) - Rizal Muttaqin; Rosida Dwi Ayuningtyas (Stability: Journal of Management and Business, 2022)
This study aims to analyze and find empirical evidence about the influence of financial literacy, religiosity, and income on investment interest in the Islamic capital market. This research is a quantitative study with data collection techniques using a questionnaire. The sample is 100 respondents who are residents of the city of semarang. The sampling technique used was simple random sampling by distributing questionnaries (randomly) to people of the city of semarang. Primary data processing uses the Statistical Package for Social Science (SPSS) analysis technique with data quality test analysis methods, classical assumptions, multiple linear regression, and hypothesis testing.The results of this study indicate that literacy has no significant positive effect on investment interest in the Islamic capital market, religiosity has a positive and significant effect on investment interest in the Islamic capital market, and income has no effect on investment interest in the Islamic capital market